Seneca, la diatriba e la ricerca di una morale austera Caratteristiche, influenze, mediazioni di un rapporto complesso - DEL GIOVANE, BARBARA (Premio Ricerca «Città di Firenze», 2015)
Within Seneca's prose, using a long-codified terminology, it is possible to identify a substratum which can be defined as diatribe. This volume aims at making up for the lack of a modern ensemble work on the cynical-stoic diatribe in Seneca's philosophy, analysing its features, influences and mediations. In response to a previous, almost purely compilatory, though systematic critical approach, this work offers an updated examination and contextualization of the individual stylistic elements bearing a seal of alleged 'diatribism'. This volume reconstructs the relationship, which is here deemed as 'complex', between the diatribe and Seneca's prose, while pursuing a research ideal which could combine moralistic contents and stylistic forms, philosophical preaching and rhetorical construction. Not least, the work aims at taking into account the extent to which the chronology of Seneca's works can be reconstructed. Among the fundamental mediations, it is possible to identify the teaching of Seneca's masters (the School of the Sextii and Attalus), the preaching of the Cynic philosopher Demetrius and Horace's poetry.